The Perception of 'Glass Ceiling' and its Impact on Career Progression of Female Managers in Malaysia - Khan, Maria (2013)
The glass ceiling is a transparent barrier that prevents women and minorities from moving up in the management hierarchy. Glass ceiling researchers have attempted to determine whether a glass ceiling exists by examining the actual promotion decision to top management, the percentage of management positions held by women in an organization, salary of male versus female managers, and ratings of potential promotion candidates to top management. The aim of this research is to investigate the variations in experiences, career identity and career development of female managers pursuing their careers in Malaysia, in order to establish, whether gender in anyway hinders career success. This research explores perceptions towards the existence of glass ceiling of female managers. The study revealed that glass ceilings or ‘invisible barriers’ exist in Malaysian work environment that hinders women from achieving senior positions. Taking the interpretive approach, this research deduces the experiences of twelve female managers working in different Industries of Malaysia from feminist perspective, and the data collected from these women were interpreted using content analysis. The findings of this research revealed that Malaysian women managers have been prone to various glass ceilings that have been directly related to their job as well as factors indirectly related to their job. Hence, the data exposed direct barriers such as perception of male employees towards the female employees, issues faced in promotions and pay disparities which led to frustration of the female managers. In addition, the higher the perceived glass ceiling, the lower one's advancement expectations, organizational commitment job satisfaction is and the higher one's intention gets to leave the firm. Fairness perceptions greatly influence the advancement aspirations and expectations, organizational commitment, and job satisfaction, and however the women didn’t show any intentions to leave the firm. The findings have important theoretical and practical implications. In conceptualizing the glass ceiling, perceptions are important above and beyond the actual status of women in the organization. Managers need to design promotion procedures that emphasize procedural fairness and diversity initiatives should be taken into account and focus on the attitudes of those employees who increase the diversity of the workplace.